2016
DOI: 10.1073/pnas.1616664113
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous central amygdala mu-opioid receptor signaling promotes sodium appetite in mice

Abstract: Due to the importance of dietary sodium and its paucity within many inland environments, terrestrial animals have evolved an instinctive sodium appetite that is commensurate with sodium deficiency. Despite a well-established role for central opioid signaling in sodium appetite, the endogenous influence of specific opioid receptor subtypes within distinct brain regions remains to be elucidated. Using selective pharmacological antagonists of opioid receptor subtypes, we reveal that endogenous mu-opioid receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…In addition to receiving gustatory information about salt, it is important to take into account that a bi‐directional opioid‐opioid signalling pathway exists between the rostral NTS and the CeA, which influences appetitive behaviours such as food intake via MORs . A similar opioid circuitry exists within the LPBN that projects to the CeA, which then activates the mesolimbic reward system involved in the motivation to consume salt and its rewarding palatability …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to receiving gustatory information about salt, it is important to take into account that a bi‐directional opioid‐opioid signalling pathway exists between the rostral NTS and the CeA, which influences appetitive behaviours such as food intake via MORs . A similar opioid circuitry exists within the LPBN that projects to the CeA, which then activates the mesolimbic reward system involved in the motivation to consume salt and its rewarding palatability …”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that central endogenous opioid peptides and receptors are involved in the regulation of salt ingestion. β‐endorphin, comprising one of these, plays a key role in the modulation of salt hedonic palatability and sodium appetite, as well as in dietary‐sodium‐overload induced sympathetic and pressor responses . Previous results from our laboratory indicated that β‐endorphin knockout mice and heterozygous mutant mice consume approximately 50% less 2% NaCl solution than wild‐type mice after sodium depletion, suggesting that β‐endorphin facilitates induced sodium appetite .…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…It is likely that NaCl intake by the CeA is mediated by endogenous opioids, given that injection of μ‐opioid receptor antagonists into the CeA significantly decreases NaCl intake appetite in mice (Smith et al. ). Studies also suggest that the PBN and CeA interact to control NaCl intake: deactivating the PBN increases NaCl intake, which is blocked by intra‐CeA injection of opioid receptor antagonists (Andrade‐Franze et al.…”
Section: Neurocircuitry Within the Central Nervous Systemmentioning
confidence: 99%